Strengthening the Capacity of Paroy Fishermen through Basic Accounting Toward a Sustainable Coastal Blue Economy - Lastri, Surna; Syamsidar, Syamsidar; Umar, Zulkifli; Anam, Budi Safatul; Susanti, Eva; Mauliansyah, Hendri (Universitas Muhammadiyah Aceh, 2025)
This community service program aimed to improve basic accounting literacy among fishermen in Gampong Paroy, Lhong Subdistrict, Aceh Besar, as part of a local economic empowerment strategy based on the blue economy concept. The activity was conducted on the coast of Gampong Paroy and involved 30 participants, including village officials and active fishermen. The methods used included educational lectures and interactive sessions, accompanied by simulations of simple bookkeeping practices relevant to small-scale fisheries. The training materials covered income and expense recording as well as basic profit-loss calculations. Evaluation results indicated increased participant understanding of the importance of financial records as decision-making tools in their fishing businesses. The program also raised awareness of data-driven business management to support sustainable coastal economic development. Recommendations include follow-up technical training and integrating similar programs into village institutional planning. This program is expected to serve as a replicable model for sustainable coastal economic empowerment in other similar regions.Keywords: fishermen, basic bookkeeping, micro-accounting, blue economy, coastal economy